Increasing Market Capitalization as The Goal of The Financial Strategy of An Investment Company - Shuyu Wu; Raju Mohammad Kamrul Alam (Communications of International Proceedings, 2021)
Recently, more and more supporters of the opinion that the main goal of the company for the owners (shareholders) is to maximize its value. This is due, first of all, to the fact that, firstly, the indicator of the company's value is a generalizing indicator, on the basis of which it is possible to judge the efficiency of the company's activity; secondly, in the conditions of developed market relations, companies often become objects of purchase and sale; thirdly, a significant proportion of modern companies are in the form of joint-stock companies, and, therefore, the well-being of shareholders also depends on the value of the company, the shares of which they own.
Keywords: Information Technology; Enterprise Capitalization; Investment Companies; Market Capitalization; Shares.